Evolving structure of the maritime trade network: Evidence from the Lloyd's Shipping Index (1890-2000) - Zuzanna Kosowska-Stamirowska; César Ducruet; Nishant Rai (Journal of Shipping and Trade (JST), 2016)
Over 90 % of the world trade volumes is being carried by sea nowadays. This figure shows the massive importance of the maritime trade routes for the world economy. However, the evolution of their structure over time is a white spot in the modern literature. In this paper we characterise and study topological changes of the maritime trade network and how they translate into navigability properties of this network. In order to do so we use tools from Graph Theory and Computer Science to describe the maritime trade network at different points in time between 1890 and 2000, based on the data on daily movements of ships. We also propose two new measures of network navigability based on a random walk procedure: random walk discovery and escape difficulty. By studying the maritime network evolution we find that it optimizes over time, increasing its navigability while doubling the number of active ports. Our findings suggest that unlike in other real world evolving networks studied in the literature up to date, the maritime network does not densify over time and its effective diameter remains constant.
Keywords: 650; Maritime trade; Network evolution; Network navigability; Graph theory